Analisis Pengaruh Free Cash Flow, Firm Size, Cash Holding, dan Sales Growth terhadap Kinerja Keuangan di Sektor Energi yang Terdaftar di BEI Tahun 2020-2024 - Y. Dedy Rangga; Katarina Agnes (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This reasech aimed to examine the“influence of free cash flow, firm size, cash holding, and sales growth on financial peformance in the energy sector listed on the Indonesia Stock Exchange form 2020-2024. This reseach employedan associative quantityative method, and the sample was selected using a purposive sampling method with parametes of companies that regularly published financial reports”for the past five years. Thus, a sample of 46 companies was obtained as research variabels.“data collection was carried out using secondary data sources through financial reportd, the data were processed using IBM SPSS version 26 software, and data analysis was carried out through descriptive statistics”test, classical assumptions, multiple linier regression, simultaneous significance test, and partial significance“tests. The results of this study indicate that thr variables”free cash flow, firm size, cash holding, and sales growth jointly influence financial performance. However, free cah flow parfially influeces financial performance, whilw firm size, cash holding, and sales growth do not affect financial performance.